2022
DOI: 10.3390/ijms23052416
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Osseointegrative Properties of Pulsed Laser-Deposited Fluorinated Hydroxyapatite Films on Nano-Zirconia for Implant Applications

Abstract: Standard zirconia implants used in restoration still present problems related to inertness and long-term stability. Various physicochemical approaches have been used to modify the implant surfaces to improve early and late bone-to-implant integration; however, no ideal surface modification has been reported. This study used pulsed laser deposition to deposit a fluorinated hydroxyapatite (FHA) film on a zirconia implant to create a biologically active surface. The film prepared was uniform, dense, and crack-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that laser surface treatment leads to a rapid temperature rise and cooling which can result in the predominant formation of a-Ti phase of a thin layer on the surface, a brittle layer consisting of a-phase Ti with an oxygenrich content. 44,45 However, our results demonstrate that Ti6Al4V after AgNP coating followed by laser surface treatment contain a high percentage of b-Ti phase and Ag, which are associated with TiAg alloy formation, despite the presence of a-phase Ti. These findings further confirm that our process provides a unique approach to selectively form TiAg alloy with a high content of oxide compounds without necessitating a change in the bulk properties of the Ti6Al4V processed material.…”
Section: Crystallographic Studymentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies have shown that laser surface treatment leads to a rapid temperature rise and cooling which can result in the predominant formation of a-Ti phase of a thin layer on the surface, a brittle layer consisting of a-phase Ti with an oxygenrich content. 44,45 However, our results demonstrate that Ti6Al4V after AgNP coating followed by laser surface treatment contain a high percentage of b-Ti phase and Ag, which are associated with TiAg alloy formation, despite the presence of a-phase Ti. These findings further confirm that our process provides a unique approach to selectively form TiAg alloy with a high content of oxide compounds without necessitating a change in the bulk properties of the Ti6Al4V processed material.…”
Section: Crystallographic Studymentioning
confidence: 59%
“…Previous studies have shown that laser surface treatment leads to a rapid temperature rise and cooling which can result in the predominant formation of α-Ti phase of a thin layer on the surface, a brittle layer consisting of α-phase Ti with an oxygen-rich content. 44,45…”
Section: Resultsmentioning
confidence: 99%
“…A direct laser melting technique was used to fabricate β-tricalcium phosphate (β-TCP) coated zirconia implants by applying a long-pulsed Nd:YAG laser of 1064 nm, thereby demonstrating that laser processes can be used to build a coat with optimum bonding and desirable mechanical properties [ 143 ]. Creation of a biologically active surface by deposition of fluorinated hydroxyapatite on zirconia implant by pulsed laser was reported by Min Li et al, 2022 [ 144 ]. Similarly, a laser-assisted biomimetic process was used for coating Calcium phosphate (CaP) on the surface of poly(ether ketone) which made the surface osteoconductive and improved its cytocompatibility [ 145 ].…”
Section: Resultsmentioning
confidence: 99%
“…The additional coating methods increase the surface hydrophilicity by taking advantage of the hydrophilic biomaterials. Biomaterials used for implant coatings are broadly classified into ceramics (Díaz-Cuenca et al 2022;Li et al 2022), polymers (Tao et al 2020;Tallet et al 2021), and metallic systems (Pham et al 2022;Yan et al 2022). However, the problems of cytotoxicity, shedding of coatings, and a lack of mechanical properties still exist.…”
Section: Introductionmentioning
confidence: 99%